Heads of Neighborhood and Citizen Performance Evaluation on Domestic Violence Allegations in Disabled Children - Rohaeni, Nani; Satiadharmanto, Deddi Fasmadhy; Nugroho, Riant (Jejaring Administrasi Publik, 2023)
Rukun Tetangga (RT) and Rukun Warga (RW) which functions to serve residents at the policy of the Village or Sub-District Government based on the Presidential Decree of the Republic of Indonesia No. 49 of 2001 concerning Structuring Village Community Resilience Institutions or Rukun Tetangga. This policy is to assist the Village/ Kelurahan in providing services and population administration directly to residents. The purpose of this study was to determine and evaluate the duties of the Head of RT/RW in the Campago Guguk Bulek Village, Mandiangin Koto Selayan, Bukittinggi, related to social problems of residents (children with disabilities and their families), which were pushed to the court to become a criminal matter. This research uses qualitative and descriptive methods. The results showed that the Head of RT/RW in the Campago Guguk Bulek Village, Mandiangin Koto Selayan, Bukittinggi provided assistance to two children with disabilities who were suspected of having experienced domestic violence (KDRT) by their grandmother and aunt, but not according to existing regulations. namely the Bukittinggi City Regional Regulation Number 11 of 2016 concerning Community Institutions in the Village Keywords: policy, neighborhood association, deliberation, evaluation, public service